PEMANFAATAN LIMBAH BIJI DURIAN (Durio zibethinus Murr) SEBAGAI BAHAN BAKU PEMBUATAN TEMPE ALTERNATIF MELALUI PROSES FERMENTASI OLEH JAMUR Rhizopus oligosporus - Yovita Harmiatun; Dr Sunarto; Marisa Gultom (Jurnal Pro-Life, 2018)
Tempe is a traditional Indonesian fermented food in which fungi, particularly Rhizopus spp. Durian seeds can be used as food alternative in the form of tempe that can add information about nutrition to the community and can create environmentally friendly. This study aims to find out how to process the waste of durian seed into an alternative tempe and tempe yeast concentration which produces the best tempe through the test of organoleptic properties. This study used Completely Randomized Design (RAL) with 3 (three) treatments and 3 (three) replicates, in which the treatments were given: control, 1 gram tempe yeast concentration and 2 gram. Organoleptic testing of durian seed tempeh viewed in terms of color, smell, texture, compactness, and taste. Organoleptic tests were used by hedonic test on a hedonic scale performed on 30 panelists. Research data were analyzed using ANAVA (Variance Analysis), followed by BNT test 95% level. The results showed that the tempe yeast concentration had significant effect on all organoleptic parameters. Testing of organoleptic tempe of durian seeds showed that most panelists liked the color, smell, texture, compactness and taste with 2 gram yeast concentration treatment.Keywords: Durian seed, tempe, yeast, organoleptic test.